The Effect of Intellectual Capital Performance on Company's Financial Performance - Bella Pramathana; Wahyu Widarjo (Universitas Muhammadiyah Malang, 2020)
This study analyzes the effect of intellectual capital performance on the company's financial performance in the current year and the following year. We use the Modified Value Added Coefficient (MVAIC) to measure the performance of company's intellectual capital. The research sample is companies listed on the Indonesia Stock Exchange (BEI) 2015-2017 which are included in the High-IC intensive industries category based on the classification of the Global Industries Classification Standard (GICS). Samples were obtained using purposive sampling technique in order to obtain 112 companies with a total of 336 observations. The data analysis technique was conducted by using panel data regression. This study results indicate that intellectual capital performance has positive and significant effect on the company's financial performance for the current year. However, it does not significantly affect the company's financial performance in the following year. This study contributes to the accounting literature development, especially the important role of intellectual capital in improving financial performance of company.